The Garland handbook of Southeast Asian music - Miller, Terry E.; Williams, Sean 1959- (Routledge, 2008)
The Garland Handbook of Southeast Asian Music is comprised of essays from The Garland Encyclopedia of World Music: Volume 4, Southeast Asia (1998). Largely revised and updated, the essays offer detailed, regional studies of the different musical cultures of Southeast Asia and examine the ways in which music helps to define the identity of this particular area. Part one provides an in-depth introduction to the area of Southeast Asia and explores a series of issues and processes, such as colonialism, mass media, spirituality, and war. The articles in this section are important in gaining historical, political, and social perspective. Part two focuses on mainland Southeast Asia, with essays representing Cambodia, Thailand, Laos, Burma, Peninsular Malaysia, Vietnam, Singapore, and the minority peoples of mainland Southeast Asia. Part three focuses on island Southeast Asia, dividing the area into three sections: Indonesia, the Philippines, and Borneo. In addition to offering a detailed study of the music of each area, it also offers recent perspectives on the gamelan and theater traditions of Indonesia. Questions for Critical Thinking at the end of each major section guide and focus attention on what issues - musical and cultural - arise when one studies the music of Southeast Asia - issues that might not occur in the study of other musics of the world. An accompanying compact disc offers musical examples from Southeast Asia.